Membangun Kreativitas Di Sekolah Dasar Desa Pagersari Melalui Program Pengembangan Media Pembelajaran - Febriani Pige Dangu; Christian Umbu. Kareju; Harnever Umbu. Galle; Theresia Nogo. Kayun; Berlian Asima Nasrani. Goltom; Maria Renita. Nahak; Agustina Valeria. Yosie; Kamaria Kamaria; Paskalia Triani. Pahut; Muhammad Fauzi Emqi; Antonius Alam Wicaksono (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2025)
Pagersari Village, located in Ngantang District, Malang Regency, East Java, is a hidden gem that offers natural beauty and rich economic potential. The diversity of agricultural and livestock products serves as the main source of income for the local community. The Community Service Program (PMT) conducted at SDN 2 Pagersari aims to enhance the quality of education and environmental awareness through various activities. One of the main activities is training in the use of the Canva application for creating educational posters, including posters on the 5 steps of proper handwashing and anti-bullying. Additionally, students also conduct training in creating Pop-Up Book learning media that explains the human body interactively. These activities not only improve graphic design skills and creativity among students but also provide a better understanding of health and hygiene. The students also participate in ecoprint training, which teaches natural fabric dyeing techniques using environmentally friendly materials, thereby raising awareness of the importance of environmental preservation. Through this program, it is hoped that students can develop a love for learning and an awareness of the importance of maintaining cleanliness while understanding health concepts in an enjoyable way. The interaction between students and the Pagersari community strengthens social bonds and benefits both parties. Thus, the PMT at SDN 2 Pagersari positively contributes to the development of local education and economy, as well as environmental preservation.